THE BASAL EMSIAN GSSP IN ZINZIL'BAN GORGE, UZBEKISTAN - Yolkin E.A.; Kim A.I.; Weddige K.; Talent J.A.; House M.R. (My University, 2001)
The agreed boundary for the Lower Devonian basal Emsian stage Global Stratotype Section and Point (GSSP) is in a section at the Zinzil'ban Gorge of the Kitab State Geological Reserve, south-southeast of Samarkand, Uzbekistan, near the base of the Khodza Kurgan Formation at the base of the Zinzil'ban Beds. The position of the boundary was selected by the Subcommission on Devonian Stratigraphy in 1989 to coincide with the level at which the conodont Polygnathus dehiscens, the successor of Polygnathus pireneae, appeared. Because of uncertainties regarding Po. dehiscens, in this paper the later species name, Polygnathus kitabicus, is used because the type material came from the GSSP, although it is thought by some to be a junior synonym of Po. dehiscens.
Keywords: Emsian; Paleozoic::Devonian::Lower::Emsian; Палеозой::Девонская::Нижний::Эмсский